(untitled) (Journal of history, 2020)
One of the great and most interesting medieval Arabic geographical works is the work of Abu Abdallah Muhammad al-Idrisi «Nuzhat al-Mushtaq fi-htirak al-Afaq». The work on the book was completed in 1154. In the work the countries of Europe, Asia and Africa, in all the known world are described in detail. Geographical work of al-Idrisi contains valuable information about the Turkic tribes: Kimek, KipchakKumanev, Oguz, Karluk, Turgeshes, Azkishah, who lived in the early Middle Ages on the territory of Kazakhstan. In the work of al-Idrisi there are also important data on the historical geography of Kazakhstan. For the first time in the history of cartography almost all modern territory of Kazakhstan is represented in «Surat al-ard». Often, al-Idrisi data are unique because they are based on written sources that not reached us. In this regard it is interesting information of «Nuzhat al-Mushtaq» about «books drawn from the words of the Turks». The author used the book Janahibn al-HakanKimek was written in Arabic probably at the end of X – XI centuries. Arab geographer describes three unique trade roads, nomadic herding and agricultural economy in Kimek society. Key words: middle Ages, Arabic source, historical geography, information, important data, territory of Kazakhstan, Turkic tribes, trade roads, nomadic herding, agricultural economy.